EARLY DETECTION OF RETINAL HEMANGIOBLASTOMAS IN VON HIPPEL–LINDAU DISEASE USING ULTRA-WIDEFIELD FLUORESCEIN ANGIOGRAPHY. Issue 4 (April 2018) - Chen, Xuejing; Sanfilippo, Christian J.; Nagiel, Aaron; Hosseini, Hamid; Mitchell, Devery; McCannel, Colin A.; Schwartz, Steven D.; McCannel, Tara A.
Abstract : Purpose: To study the use of ultra-widefield fluorescein angiography (UWF FA) in the detection and management of retinal capillary hemangioblastomas in patients with von Hippel–Lindau disease. Methods: This is a retrospective study of patients with von Hippel–Lindau disease who underwent UWF FA using the Optos camera at a single center from June 2009 to May 2015. The clinical use of UWF FA was reviewed, and the number of hemangioblastomas identified on UWF FA was compared with ophthalmoscopy and a simulated seven standard field (7SF) FA montage. Results: Twenty eyes of 10 patients were identified. Only 33% of lesions seen on UWF FA were also found on ophthalmoscopy, and 88% of lesions visualized on UWF FA were located outside the 7SF overlay. In 5 eyes that had gaze steering, 18% of lesions could be visualized only on gaze-steered images. For the 14 eyes with data available, 6 had procedures recommended and 8 eyes observed based on data from UWF FA. One of 20 eyes had a lesion on ophthalmoscopy that was missed by imaging. Conclusion: Ultra-widefield FA using the Optos camera is helpful for the evaluation and management of patients with von Hippel–Lindau disease. The UWF FA with gaze steering appears to detect more hemangioblastomas than ophthalmoscopy and conventional angiography. Abstract : Supplemental Digital Content is Available in the Text.Patients with von Hippel–Lindau disease can suffer devastating vision loss from complications of retinal capillary hemangioblastomas. The authors found that ultra-widefield fluorescein angiography, especially with gaze steering, provides useful information for the evaluation and management of these eyes and can identify more hemangioblastomas than a simulated seven standard field fluorescein angiography.